Effect of Vitamin A, Zinc and Vitamin E Supplementation on Immune Response in Seropositive Leprosy Subjects - Rahfiludin, M. Zen; Pramono, Adriyan; Setiani, Onny (Pakistan Journal of Nutrition, 2015)
The immune response plays an important role in leprosy prevention. Here we analyzed the effect of vitamin A, zinc and vitamin E supplementation on the immune response in seropositive leprosy patients by measuring serum levels of retinol, zinc, α-tocopherol, interferon gamma (IFN-γ) and interleukin-2 (IL-2). Subjects were randomly divided into either the treatment or control group. The treatment group received high dose vitamin A once and a daily dose of Zn and vitamin E supplementation for 45 days, while the control group received pills that were identical in appearance but lacked supplements. Supplement consumption compliance was recorded weekly. After 45 days of supplementation, IFN-γ and IL-2 levels were measured again. Upon study initiation both groups had normal retinol, zinc and α-tocopherol serum levels. After 45 days, serum levels of retinol and α-tocopherol increased only in the supplementation group (p = 0.046 and p = 0.033, respectively), while zinc serum levels decreased in both the supplementation (p = 0.001) and placebo (p = 0.000) groups. IFN-γ levels decreased slightly in the supplementation group, although the change was not significant (p = 0.098). Meanwhile, IFN-γ levels in the control group decreased significantly (p = 0.022). IL-2 levels decreased slightly in both the supplementation and placebo groups, but the changes were not significant (p = 0.421 and p = 0.556, respectively). Together our results indicate that supplementation with zinc and vitamins A and E could be a useful alternative therapy for maintaining immune response of seropositive leprosy patients.